2020
DOI: 10.1016/j.ccell.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Proteomic Profiling Uncovers a Targetable GNAS/PKA/PP2A Axis in Small Cell Lung Cancer Stem Cells

Abstract: Highlights d PKA inhibition or PP2A activation inhibits SCLC growth d The GNAS/PKA axis promotes SCLC growth d Proteomics studies uncover widespread PKA targets and downstream signaling networks d PKA activation promotes a cancer stem cell state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 111 publications
8
70
1
Order By: Relevance
“…Related studies have delineated the essential role of PKAc as its effector (Coles et al, 2020;Patra et al, 2018). Here, we define the context of genetic alterations in PRKACA and PRKAR1A that result in PKAc activation in cancer and a set of conserved pathways downstream oncogenic PKAc signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have delineated the essential role of PKAc as its effector (Coles et al, 2020;Patra et al, 2018). Here, we define the context of genetic alterations in PRKACA and PRKAR1A that result in PKAc activation in cancer and a set of conserved pathways downstream oncogenic PKAc signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the plasticity of CSCs, Stationary CSCs may produce cycling CSCs, leading to cancer recurrence [21] . Studies have shown that PKA activation promotes CSC state in small cell lung cancer [22] . In colorectal cancer, CSC evades treatment-mediated DNA damage by changing cell cycle checkpoints, increasing DNA damage repair capabilities, and effectively removing reactive oxygen species [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hijazi and colleagues used chemical phosphoproteomics to reveal that while PIK3CA wild-type cells seem to depend on MAPK pathway activation, PIK3CA mutant cells more predominantly rely on AKT and mTOR signaling outputs for survival [ 271 ]. Moreover, phosphoproteomics analysis identified the protein kinase A (PKA)-regulated signaling network as pro-tumorigenic circuitry in G-protein α subunit (GNAS)-mutated small cell lung cancer cells [ 272 ]. Through phosphoproteomics, we recently found that the loss of PTEN protein phosphatase activity leads to an enrichment of phospho-peptides regulated by the glucocorticoid receptor, GR, and confirmed that GR activation sensitizes mutant PTEN cells to death [ 139 ].…”
Section: How Can Technological Advances Assist With the Identificamentioning
confidence: 99%